ANTENNE RESEAU A COMMANDE DE PHASE - N. Amar Touhami; M. Gueye; A. Zakriti; M. Boussouis; A. Tribak (European Scientific Journal, ESJ, 2013)
Phased array antennas are known for their capability to steer the beam pattern electronically with high effectiveness, managing to get minimum side-lobe levels and narrow beamwidths. Normally phase shifters are the devices in a phased array antenna that allow the radiated beam to be steered in the direction. The objective of this research is to investigate a phase shifter in a linear antenna array for angle scan.A microstrip antenna array is used since it is simple to design and fabricate. The phase shifter is provided using low pass filter. Ansoft Designer Software is used to simulate a low pass filter and Ansoft Ensemble Software to simulate phased array antenna